Lipoprotein (a): More than a bystander in the etiology of hypertension? A study on essential hypertensive patients not yet on treatment - Ali Ghorbani; Mahmoud Rafieian-Kopaei; Hamid Nasri (Society of Diabetic Nephropathy Prevention, 2013)
Background: Hypertension (HTN) is a very common disorder with a substantial impact on public health because of its complications. Objectives: To study the association of serum lipoprotein(a) [Lp(a)] elevation with essential hypertension (eHTN). Patients and Methods: This study was conducted on a group of essential hypertensive patients. Laboratory exams consisting of serum creatinine and Lp(a) were measured. Results: Ninety five essential hypertensive patients were enrolled to the study. Serum LP (a) in patients was 46.5±20. In patients an inverse correlation between serum Lp(a) andcreatinine clearance was seen (r = -0.175 p<0.05). There was a significant correlation between serum Lp(a) and age (r =0.191 p<0.05) or duration of HTN (known duration of hypertension period) (r =0.362 p<0.05). Conclusions: Our data suggest that Lp(a) may be involved as a cofactor in essential hypertension, with a mechanism that remains to be elucidated.